Obstetric outcomes of young women following in-vitro fertilization: a case-control study - Gilad Karavani; Henry H. Chill; Aharon Dick; Marva Bergman; Tal Imbar; Sorina Grisaru-Granovsky; Assaf Ben-Meir (BMC, 2022)
Abstract Background Women undergoing in-vitro fertilization (IVF) treatments are at increased risk for maternal and neonatal complications compared to women who conceive spontaneously. Though spontaneous pregnancies of young women and adolescents have an increased risk for adverse maternal and neonatal outcomes, pregnancy outcomes of this age group, following IVF treatment have been scarcely reported. The aim of this study was to report maternal and neonatal outcomes of young women who conceived following IVF compared to women in the same age group with spontaneous conception. Methods We performed a multicenter case-control study. The study group included women aged 17-25 years who conceived by IVF with an ongoing singleton pregnancy. For the purpose of the study, a control group matched (1:2 ratio) for maternal age at delivery and parity was constructed. Demographic, medical history, pregnancy related characteristics and maternal and neonatal outcomes were compared between groups. Finally, factors associated with spontaneous vaginal delivery were assessed for the entire cohort using a univariate and multivariate logistic regression model. Results Between 2005 and 2021, we identified 80 women aged 19-25 years who conceived by IVF. A control group of 160 women was matched to the study group by age and parity. The unmatched maternal characteristics and pregnancy associated complications were similar among the groups. However, the IVF group had a significantly higher rate of induction of labor (48.1% vs. 26.6%, p = 0.001), meconium-stained amniotic fluid (27.6% vs. 14.1%, p = 0.025), prolonged second stage of labor (26.0% vs. 7.3%, p = 0.001) and operative vaginal delivery (22.5% vs.12.5%, p = 0.048). Neonatal outcomes were for the most part comparable; nevertheless, we found a higher rate of neonates with an umbilical artery pH < 7.1 in the IVF group (9.8% vs. 0.0%, respectively; p = 0.022). A logistic regression analysis for spontaneous vaginal delivery (vs. cesarean or operative vaginal deliveries) found that spontaneous onset of labor (vs. induction of labor) (OR = 2.08; 95% CI = 1.07-4.05, p = 0.03) was positively associated with spontaneous vaginal delivery while prolonged second stage of labor (OR = 0.35; 95% CI = 0.13-0.95, p = 0.04) was negatively associated with this parameter. Conclusion Young women who conceive by in-vitro fertilization are expected to reach favorable pregnancy outcomes, comparable to women who conceived spontaneously.